Analisis Kualitas Produk, Persepsi Harga, Dan Kepuasan Konsumen Pada Produk Khong Guan - Vara Zahira Septifia; Natasya Amalia (Jurnal Multidisipliner Bharasumba, 2026)
The increasingly dynamic competition in the biscuit industry is driving companies to continuously maintain product quality and set prices that align with the value perceived by consumers. This study aims to examine consumer perceptions of product quality, price perceptions, and consumer satisfaction with Khong Guan products. The study employed a descriptive qualitative approach, involving 15 informants selected through purposive sampling. Data were collected through semi-structured interviews and then analyzed using the interactive analysis model developed by Miles, Huberman, and Saldaña, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that taste, product safety, variety, and packaging are the aspects that most influence consumer satisfaction. Most informants assessed that Khong Guan’s prices are commensurate with the quality received and remain competitive with similar products. Consumer satisfaction is also reflected in the tendency to make repeat purchases and provide recommendations to other consumers.